Mapping Global Diversity Research in Elementary School (2016-2025): A Scopus Based Bibliometric Analysis - Nita Febriani; Sekar Purbarini Kawuryan; Albi Anggito (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
Global diversity is a crucial aspect in elementary education to form a generation that can adapt in a multicultural society while maintaining local cultural identity. Although this topic is increasingly relevant in the era of globalization, there has been no comprehensive mapping of the development of research on it at the elementary school level. This study aims to analyze research trends on global diversity in elementary schools through a bibliometric approach. Data were collected from the Scopus database (2016-2025) using the keywords "Global Diversity AND Elementary School", then analyzed with VOSViewer to map publication productivity, geographical distribution, researcher collaboration, and research theme networks. This study reveals several challenges, such as the inequality of research distribution between countries and the lack of exploration of contextual learning strategies. The implication is that it is necessary to strengthen international collaboration, develop local culture-based learning models, and education policies that support the implementation of global diversity in elementary schools. These findings open up opportunities for further research to explore the integration of local wisdom in the curriculum or the impact of technology on understanding diversity. Global diversity is an important aspect of primary education in shaping an adaptive generation in a multicultural society without losing local cultural identity. However, there has been no comprehensive mapping of research trends at the primary school level. This study analyzes the development of global diversity research through a bibliometric approach using Scopus data (2016–2025) with the keywords “Global Diversity AND Elementary School.” The analysis using VOSViewer maps publication productivity, geographical distribution, researcher collaboration, and research themes. The study reveals two main findings: (1) disparities in research distribution among countries, and (2) limited studies on contextual learning strategies. The study's implications emphasize the need for international collaboration and the development of culturally-based learning models. Additionally, this research identifies opportunities for further research, such as integrating local wisdom into the curriculum and the role of technology in diversity education.